A Public Health Service-Learning Capstone: Ideal for Students, Academia and Community - Mackenzie, Sara L. C.; Hinchey, Deborah M.; Cornforth, Kathryn P. (Frontiers in Public Health, 2019)
Undergraduate public health degree programs strive to educate students to improve the health of communities. As such we have an obligation to develop curricula that push students to think critically about their perspectives, examine assumptions and provide supported opportunities to apply their academic learning. In addition, curricula ideally develop and nurture students' sense of civic responsibility. Community-engaged learning provides opportunities for students to interact with populations with a range of needs and different perspectives. Students need to be prepared to engage ethically and respectfully, while thinking critically about and reflecting on their roles in these communities. Service-learning is a high-impact practice that combines community service with structured academic learning, including preparation and reflection. In line with public health community based work, a key aspect of service-learning is the intentional development of community partnerships to ensure that students are filling the needs defined by the communities themselves. Accreditation criteria may guide what is taught but say little about how it should be taught. However, how we teach matters. Service-learning is a high impact practice that not only aligns well with the goals and objectives of a culminating senior experience but shares many of the values of the discipline of public health. This paper analyzes the use of service-learning in the development and delivery of the University of Washington School of Public Health undergraduate Public Health-Global Health majors’ culminating experience. We describe the course learning objectives, structure and assessment tools. In addition, we present quantitative and qualitative results on the impact of the course. We argue that it is feasible, sustainable and beneficial to students and communities when the high impact practice of service-learning is used in delivery of a culminating senior experience.